Assessment of soil mesofauna diversity, dominance, and environmental conditions in paddy field ecosystems with recommendations for sustainable agricultural practices - Numa, Alya Mahirotun; Susanto (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The diversity and dominance of soil mesofauna are influenced by environmental factors such as soil temperature, pH, humidity, and texture. This study aims to analyze the soil mesofauna community, including species count, diversity, and dominance, and evaluate the environmental quality of rice fields in Pliken Village, Kembaran District, Banyumas Regency. Methods: The research was conducted using a survey method from January to June 2023. Soil samples were collected from three different locations (west, north, and south) with a one-month interval. Sampling was carried out twice a day, in the morning (06:0–008:00 Western Indonesia Time) and evening (18:00–20:00 Western Indonesia Time). Findings: A total of 820 individuals from 13 species, 11 families, and 9 orders of soil mesofauna were recorded. Solenopsis invicta (Red Ants) had the highest count (332 individuals), while Cimex sp. and Pulex sp. had the lowest (2 individuals each). The Shannon-Wiener diversity index ranged from 1.19 to 1.86, averaging 1.52, indicating moderate diversity. The Simpson dominance index ranged from 0.150 to 0.531, averaging 0.300, suggesting no species dominance. Environmental factors such as air temperature (22–28°C), soil temperature (23–28°C), and soil pH (6.1) were within optimal ranges for mesofauna life. However, humidity levels varied between 20–65%, with lower values in the dry season, potentially affecting mesofauna survival. Conclusion: The rice fields of Pliken Village support a moderately diverse soil mesofauna community with no dominant species. The environmental conditions are generally favorable, except for humidity fluctuations, which may impact mesofauna populations. Sustainable land management practices, such as reducing excessive pesticide use, are recommended to maintain soil fertility and biodiversity. Novelty/Originality of this article: This study provides a comprehensive assessment of soil mesofauna diversity and environmental quality in rice fields, offering valuable insights into the impact of agricultural practices on soil ecosystems. The findings highlight the need for sustainable land management to preserve soil biodiversity and fertility.